Identification of specific recommendations for prehospital stroke care associated with shorter door-to-CT times – An analysis of Get with the Guidelines-Stroke registry and prehospital data - Dylla, Layne; Higgins, Hannah M.; Wham, Courtney D.; Leppert, Michelle; Ravare, Brandy C.; Jeppson, Kerri A.; Bina, Heather T.; Monte, Andrew A.; Poisson, Sharon N. (Frontiers in Stroke, 2024)
Objective: Full compliance with American Heart Association (AHA) recommendations for prehospital care of stroke patients remains low. This study aims to identify components of prehospital care associated with shorter door-to-CT times. Methods: Data from a comprehensive stroke center’s Get with the Guidelines-Stroke Registry was supplemented by prehospital medical records for ischemic stroke patients between January 1, 2018, and December 31, 2020. Descriptive statistics and multivariable linear regression modeling evaluated door-to-CT times for encounters compliant with AHA recommendations. Results: There were 621 ischemic stroke patients who presented via a prehospital provider, 452 of whom presented from the scene. Without adjusting for potential confounders, shorter door-to-CT times were observed with EMS documentation of a last known well time, measurement of a blood glucose lever, prenotification of suspected stroke, or full compliance with AHA recommendations. Documentation of classic stroke signs, but not documentation of a prehospital stroke scale, was also observed to have shorter door-to-CT times compared to encounters where this did not occur. Conclusions: During prehospital care of stroke, documentation of classic symptoms, obtaining a last known well time or time of symptom onset, obtaining a blood glucose level, prenotification of the receiving hospital of suspected stroke, and full guideline-compliance are associated with shorter door-to-CT times. Further studies are needed to understand if a shift in prehospital provider education, focusing on these key components of care, could lead to earlier diagnosis and treatment of acute stroke.